Essential role of autoactivation circuitry on Aurora B-mediated H2AX-pS121 in mitosis - Midori Shimada (Nature Portfolio, 2016)
Aurora B activation at the centromere is critical for faithful chromosome segregation in mammals. Here the authors show that Aurora B-mediated phosphorylation of histone H2AX at serine 121 is essential for Aurora B auto-activation circuitry at centromeres, ensuring proper chromosome segregation.